Perfil imunológico de indivíduos soropositivos de uma família com alta prevalência de infecção pelo HTLV-1 e alta incidência de doenças dermatológicas - Adriano Santos Cloves (2010)
The HTLV-1 (Human T-lymphotropic virus 1) is a retrovirus that causes an aggressive type of leukemia, the Adult T Leukemia/Lymphoma and a neurodegenerative inflammatory syndrome entitled HTLV-1-Associated Myelopathy/Tropical Spastic Paraparesis (HAM/TSP). The virus can also cause dermatological clinical disorders, particularly on HTLV-1 seropositive persons from endemic areas. Nevertheless, the immunopathogenic mechanisms underlying this different pattern of disorders are not fully understood. Thus, in this present study, the immunological profile of persons from a familiar cluster with high prevalence of infection and dermatological disorders was evaluated. To achieve our goal, the reactivity against HTLV-1 antigens from MT-2 cells was evaluated by a in house Western assay and a Immunoblot assay. The anti-Tax reactivity was evaluated by an in-house ELISA with a recombinant Tax produced in our laboratory. Additionally, the Th1 and Th2 responses were evaluated by assessment of chemokines, and a neurotrophin levels on sera samples from the familiar cluster and the GIPH cohort performed. The results revealed a distinct reactivity profile against HTLV-1 antigens for persons from the familiar cluster when compared to asymptomatic carriers and HAM/TSP patients from GIPH cohort. The analysis of Th1 and Th2 responses demonstrated that the GIPH cohort and the familiar cluster present a Th1- predominant response with higher levels of CXCL9/MIG, CXCL10/IP-10, CCL5/RANTES and TNF-α receptors (sTNFR1 and sTNFR2). The BDNF presented higher levels on sera samples from the familiar cluster, contrasting to HAM/TSP patients from GIPH cohort which presented lower BDNF levels. On the whole, these results strongly suggest that the familiar cluster presents a distinctive immunological profile, different from asymptomatic carriers and HAM/TSP from GIPH cohort, cohoborating the hypothesis that the dermatological disorders represent a divergent and singular pole among the many HTLV-1 associated diseases.